Pengaruh Biaya Produksi Dan Biaya Pemasaran Terhadap Laba Bersih Perusahaan (PT Unilever Indonesia Tbk Yang Terdaftar Pada BEI Periode 2014– 2023) - Tiara Aprillia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the effect of production costs and marketing costs on the net profit of the company PT Unilever Indonesia Tbk which is listed on the Indonesia Stock Exchange (BEI) for the 2014-2023 period. The method used in this research is descriptive method. The data collection technique is carried out through secondary data, namely data obtained indirectly, data taken in the form of published data through the official website of the Indonesian Stock Exchange and the PT Unilever Indonesia website. The analytical methods used in this research are descriptive analysis, regression analysis with normality test, multicollinearity test, heteroscedasticity test and autocorrelation test, multiple linear regression test and hypothesis testing using the t test, f test and analysis of the coefficient of determination.Based on the results of research conducted, it shows that simultaneously, the variables of production costs and marketing costs have a significant effect on the net profit price. Partial test results show that the production cost variable has a significant effect on net profit, but partial test results for the marketing cost variable show that this variable does not have a significant effect on the net profit of the company PT Unilever Indonesia Tbk for the 2014-2023 period.